Limited Utility of Self-made Oxygen Generators Assembled From Everyday Commodities During the COVID-19 Pandemic. (12th May 2023) - Limper, Ulrich; Klaas, Lena; Köhler, Markus; Lichte, Daniel; Maldonado Samaniego, Nelson J; Suarez, Jose I; Jordan, Jens; Hoffschmidt, Bernhard
Abstract: The current COVID-19 pandemic has aggravated pre-existing oxygen supply gaps all over the world. In fact, oxygen shortages occurred in affluent areas with highly developed healthcare systems. The state-of-affairs created much suffering and resulted in potentially preventable deaths. Meanwhile, several international activities have been initiated to improve oxygen availability in the long-term by creating new networks of oxygen plants and supply channels. However, disasters such as the current pandemic may require rapid, autarkic oxygen production. Therefore, we determined whether oxygen resilience could conceivably be improved through self-made oxygen generators using material that is easily available even in remote areas. The team comprised engineers and physicians with hands-on experience in low- and middle-income countries. We constructed and tested self-made setups for water hydrolysis and membrane-based oxygen purification. We must conclude, however, that the massive amounts of oxygen patients with COVID-19 require cannot be reasonably met with such simple measures, which would require high efforts and hold potential risks.